Temporal dynamic characteristics of human monkeypox epidemic in 2022 around the world under the COVID-19 pandemic background - Cao, Yanxiang; Li, Meijia; Haihambo, Naem; Wang, Xinni; Zhao, Xixi; Wang, Bin; Sun, Meirong; Guo, Mingrou; Han, Chuanliang (Frontiers in Public Health, 2023)
Background: The reemergence of the monkeypox epidemic has aroused great concern internationally. Concurrently, the COVID-19 epidemic is still ongoing. It is essential to understand the temporal dynamics of the monkeypox epidemic in 2022 and its relationship with the dynamics of the COVID-19 epidemic. In this study, we aimed to explore the temporal dynamic characteristics of the human monkeypox epidemic in 2022 and its relationship with those of the COVID-19 epidemic. Methods: We used publicly available data of cumulative monkeypox cases and COVID-19 in 2022 and COVID-19 at the beginning of 2020 for model validation and further analyses. The time series data were fitted with a descriptive model using the sigmoid function. Two important indices (logistic growth rate and semi-saturation period) could be obtained from the model to evaluate the temporal characteristics of the epidemic. Results: As for the monkeypox epidemic, the growth rate of infection and semi-saturation period showed a negative correlation (r=0.47, p=0.034). The growth rate also showed a significant relationship with the locations of the country in which it occurs (latitude (r=-0.45, p=0.038)). The development of the monkeypox epidemic did not show significant correlation compared with the that of COVID-19 in 2020 and 2022. When comparing the COVID-19 epidemic with that of monkeypox, a significantly longer semi-saturation period was observed for monkeypox, while a significant larger growth rate was found in COVID-19 in 2020. Conclusions: This novel study investigates the temporal dynamics of the human monkeypox epidemic and its relationship with the ongoing COVID-19 epidemic, which could provide more appropriate guidance for local governments to plan and implement further fit-for-purpose epidemic prevention policies.